Attractiveness and efficiency of European universities as hosts for Marie Curie grant holders - Martin Falk; Eva Hagsten (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This study provides novel empirical insights into the attractiveness of European Universities for Marie Sk±odowska-Curie Actions (MSCA) grant holders and investigates how efficient universities are in this respect relative their potential. To explore the attractiveness, factors explaining both the probability of a university being chosen as host for a MSCA grant holder as well as the number of grants are estimated by use of a zero-inflated negative binomial model. The analysis is based on the universe of MCSA grant holders from the EU Cordis H2020 database for the year 2017, linked to the 2016 information from the Times Higher Education database on 390 European universities. Approximately half of the universities hosts MSCA fellows in 2017. Estimations based on the zero-inflated negative binomial model reveal that research performance, share of international students as well as size of the university are significant factors of importance for the probability of attracting MSCA grant holders. Research performance, citations and the student staff ratio are significant predictors for the extent of grant holders. A comparison of actual and potential number of grant holders attracted reveals that some universities mainly in the Northwest of Europe (University of Copenhagen, KU Leuven, Eindhoven University of Technology, University of Antwerp, Aarhus University, University of Oslo, University of Vienna, University of Birmingham and University of Leeds) all receive far more MSCA fellows than would have been expected given their attributes, while Imperial College London and University College of London receive fewer.
Keywords: I20; I23; 330; higher education; academic mobility; postdoctoral researchers; universities; count data model.